Attenuation Measurement Using the IF Substitution Method in the Frequency Range of 9 kHz to 10 MHz - Joo-Gwang Lee; Tae-Weon Kang; Young-Pyo Hong; Jae-Yong Kwon (Journal of Electromagnetic Engineering and Science)
Using the intermediate frequency (IF) substitution method, this study establishes a low-frequency attenuation measurement standard operating in the 9 kHz to 10 MHz frequency range. We designed and fabricated a low-frequency attenuation measuring instrument using a mixer that converts the input radio frequency signal into an output IF of 1 kHz. When varying the attenuation of a variable attenuator under test, an attenuation of up to 100 dB was measured. The IF output of the mixer was measured using a spectrum analyzer as the receiver. The receiver’s performance was evaluated using an inductive voltage divider whose measurement capability is traceable to the electrical measurement standard. The measurement uncertainty, which accounts for uncertainty sources such as the performance of the receiver, mismatch, and mixer nonlinearity, was evaluated to be 0.005 dB to 0.058 dB (k = 2) in the attenuation range of 10 dB to 100 dB.